A rule-driven multi-path routing algorithm with dynamic immune clustering for event-driven wireless sensor networks - Ding, Yongsheng; Chen, Rui; Hao, Kuangrong (Neurocomputing (Amsterdam), 2016)
In order to save energy for event-driven wireless sensor networks (WSNs) applied to emergency monitoring, a rule-driven multi-path routing algorithm with dynamic immune clustering (RDICMR) is proposed. The RDICMR algorithm is executed under the driven of condition rules and implementation rules. By applying the working mechanism of the biological immune system to the event-driven dynamic clustering algorithm for WSNs, where event as antigen, the records of clusters and routing paths of past events in the node׳s memory as antibodies, antibodies have the function of collecting and preserving memories, as such it is convenient to response to antigens that are similar to the previous antigen timely. When similar events happen and satisfy the affinity and energy rules, the sensor nodes can directly call antibodies in the memory to build clusters of events and transfer data quickly. Besides, we change the cycle of the network dynamically according to the updating cluster cycle rule. The proposed RDICMR algorithm saves a lot of energy in the process of building clusters and data transmission, increases the amount of data transmission and prolongs the lifetime of the network.